2003
DOI: 10.1136/oem.60.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Fluid losses and hydration status of industrial workers under thermal stress working extended shifts

Abstract: Aims: To assess whether workers under significant thermal stress necessarily dehydrated during their exposure and whether "involuntary dehydration" was inevitable, as supported by ISO 9866 and other authorities. Other objectives were to quantify sweat rates against recommended occupational limits, to develop a dehydration protocol to assist with managing heat exposures, and to understand the role of meal breaks on extended shifts in terms of fluid replacement. Methods: A field investigation to examine the flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 14 publications
2
92
0
7
Order By: Relevance
“…This requires heat transfer to the skin via cutaneous vasolidation and the loss of fluid which, if not replaced, can result in dehydration. Previous study reported that sweat rates > 1 L/hour can be expected of workers in hot environment (Brake and Bates, 2003;. The acute implication of dehydration is the result of a depleted blood volume and the consequent cardiovascular strain.…”
Section: Discussionmentioning
confidence: 96%
“…This requires heat transfer to the skin via cutaneous vasolidation and the loss of fluid which, if not replaced, can result in dehydration. Previous study reported that sweat rates > 1 L/hour can be expected of workers in hot environment (Brake and Bates, 2003;. The acute implication of dehydration is the result of a depleted blood volume and the consequent cardiovascular strain.…”
Section: Discussionmentioning
confidence: 96%
“…Miners' hydration is important in underground hot environments, since dehydration reduces the physical capacity to work efficiently [8]. Involuntary dehydration does not occur in well-informed miners [9]. As Indian miners are very poorly educated and consequently too ignorant about their health status to cope with situations at work, the need to address the degree of stress on the cardiovascular system and to measure its functional capability has been felt.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have measured the thermal strains of workers in heat environments, such as steel 21) , coal mine 22,23) and construction 24) , but the thermometric methods were poor. We also measured the ambient temperatures at the shoulder where workers felt hot.…”
Section: Discussionmentioning
confidence: 99%